Pandangan Orientalis terhadap Hukum Islam - Ma'mun Efendi Nur (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2011)
This paper will explain about the Orientalist view of Islamic law. From this paper can be concluded that despite the Orientalist see the truth of Islam as a Samawi religion revealed to the prophet Muhammad that includes all aspects including the legal aspects of the norms and values derived from the Koran remains to twist the facts are subjective to undermine Islam by Muslims themselves on the grounds of scientific methodologies that now a rise to anticipate them GAZW Fikry (Intellectual war). But behind it there are also some attempts of some of the orient lists objective in presenting Islam as religions which resources from the Holy Book, Al-Qur’an. View of some orient lists on the Islamic law which was considered affected by the law Rum, because look at the element of conformity in one case, which incidentally Rum first law on the existence of Islamic law based on the Quran